Science and The Character of Islam Rahmatan Lil ‘Aalamien: Junior High School Learning Model in Central Java, Indonesia - Salafudin Salafudin; M Yasin Abidin (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2019)
This study aimed to analyze the Science Learning Model for Junior High School that creates the character of Islam Rahmatan Lil ‘aalamien (Islam as the mercy to all worlds) and to describe and to analyze the implementation of science learning in Junior High School in Central Java. This study focused on two schools in Pekalongan and Tegal that create the character of Islam Rahmatan Lil ‘aalamien. The approach used in this study was developmental research. The result of research showed: (1) teacher having used learning model leading to the creation of character, (2) the development of MPSMK IRLA and its learning set developed building on the finding of learning model implemented so far in SMPIT Lukmanul Hakim Slawi of Tegal Regency and SMP 17 Pekalongan and the analysis of the need for science learning model creating the character of Islam Rahmatan Lil ‘alamien, and (3) the implementation of MPSMK IRLA in the trial conducted in SMPIT Lukmanul Hakim Slawi of Tegal regency finding that the average assessment for the character of IRLA belonging to very culturing.